Portuguese vernacular architecture : the contribution of vernacular materials and design approaches for sustainable construction - Fernandes, J. (2015)
Vernacular architecture is characterized by a type of formal expression, which has been developed in response to a number of factors – geographic, climatic and economic – characterizing the local area or region. Despite the fact that Portugal is a small country, there are many different architectural approaches and a range of techniques have been employed in different regions to mitigate the effects of climate. These vernacular approaches have the potential for further development and could be adapted in response to contemporary needs. In this paper, a range of different passive solar techniques used in Portuguese vernacular architecture to provide comfort is presented. The specific focus is on the effectiveness of passive cooling strategies (namely, high thermal inertia, use of light colours and courtyards), and the findings of a case study in which the thermal performance during the summer of a vernacular residential building located in the south of Portugal are presented.